How did Bursaphelenchus nematodes acquire a specific relationship with their beetle vectors, Monochamus? - Kirino, Haru; Maehara, Noritoshi; Shinya, Ryoji (Frontiers in Physiology, 2023)
For insect-borne pathogens, phoretic ability is important not only to spread more widely and efficiently but also to evolve virulence. Bursaphelenchus xylophilus, the causal agent of pine wilt disease, is transmitted by the cerambycid beetle Monochamus alternatus, which is associated with pine tree host. Their specific phoretic ability to appropriate vectors depending on their life cycle is critical for efficient transfer to the correct host and is expected to enhance virulence. We evaluated how B. xylophilus acquired a specific relationship with M. alternatus with a focus on Bursaphelenchus okinawaensis, a close relative of B. xylophilus that has evolved a relationship with a cerambycid beetle vector. Bursaphelenchus okinawaensis has a single dispersal stage (dauer) larva (third-stage dispersal [DIII] larva), whereas B. xylophilus has two distinct dispersal stages (DIII and fourth-stage dispersal [DIV] larva). Also, the dauer formation in B. okinawaensis is not completely dependent on its beetle vector, whereas DIV larvae of B. xylophilus are induced by volatile from the beetle vector.We investigated the induction conditions of dauer larvae in B. okinawaensis and compared to with B. xylophilus. The dauer percentages of B. okinawaensis significantly increased when the nematode population on the plate increased or when we propagated the nematodes with a crude extract of cultured nematodes, which likely contained dauer-inducing pheromones. In addition, dauer formation tended to be enhanced by the crude extract at high temperatures.Furthermore, when we propagated the nematodes with M. alternatus pupae until the beetles eclosed, B. okinawaensis significantly developed into dauer larvae. However, only 1.3% of dauer larvae were successfully transferred to M. alternatus, the rate lower than that of B.xylophilus. DIII and DIV of B. xylophilus were induced by increasing the nematode population and the presence of the beetle vector, respectively. These results suggest that B. okinawaensis has acquired specificity for the cerambycid beetle through dauer formation, which is efficiently induced in the presence of the beetle, and the DIV larval stage, exclusive to the 'xylophilus' group, may be crucial for high transfer ability to the beetle vector.